E-Modul Matematika Berbasis Penemuan Terbimbing dengan Pendekatan STEAM Untuk Memfasilitasi Kemampuan Pemecahan Masalah - Siti Rosmita; Revita, Rena (LPPM Universitas Advent Indonesia, 2024)
The purpose of this research is to develop a guided discovery-based mathematics e-module with a STEAM approach to facilitate students' mathematical problem solving skills that meet the valid, practical, and effective criteria using the ADDIE development model. The subjects in this study were validators including lecturers and teachers as well as students of SMP Negeri 1 Tandun. The object of the research is a guided discovery-based math e-module with a STEAM approach. Data collection used questionnaire and test techniques. The research instruments consisted of validity test instruments in the form of instrument validation sheets, e-module validation sheets by learning material and educational technology experts, practicality test instruments in the form of student response questionnaire sheets, and effectiveness test instruments in the form of posttest questions. The data analysis techniques used are quantitative and qualitative data analysis techniques. Based on the results of the data analysis, it was concluded that the guided discovery-based mathematics e-module with the STEAM approach was declared to have met the criteria of being very valid, very practical, and also effective. This shows that the math e-module based on guided discovery with the STEAM approach to facilitate students' mathematical problem solving skills that has been developed is suitable to be used as teaching material in the learning process.